Autoimmune bullous diseases in non‐HIV Kaposi's sarcoma: a retrospective study in a large cohort of patients. (28th May 2018) - Tourlaki, A.; Genovese, G.; Guanziroli, E.; Scoppio, B.M.; Berti, E.; Brambilla, L.
Abstract: Background: Kaposi's sarcoma (KS) is a rare endothelial neoplasm caused by the human herpesvirus 8 (HHV‐8). Its risk is increased in immunocompromised patients, including those undergoing immunosuppressive therapy for autoimmune bullous diseases. Conversely, HHV‐8 infection has been hypothesized to be a triggering factor of bullous diseases, especially pemphigus. Given the fact that both KS and autoimmune bullous diseases have a low incidence in the general population, it could be expected that the association between these disorders would be exceptional. Objectives: To assess the frequency of bullous diseases in a large cohort of non‐HIV KS patients and to describe our experience concerning the clinical features, natural history and treatment options in this setting. Methods: We performed a retrospective review of all patients with non‐HIV KS in association with bullous disease followed at our department between 1990 and 2016. Medical records were reviewed for demographics, medical history, clinical characteristics and treatment. Results: Among 1362 patients with classic or iatrogenic KS, 14 (1.03%) also suffered from bullous disease. The mean age at diagnosis of both disorders was 85.8 years with a male/female ratio of 9 : 5. Among these 14 cases, nine (0.66%) were associated with bullous pemphigoid (BP), three (0.22%) with localized BP and two (0.15%) with pemphigus vulgaris. Seven had developed a bullous disease after being diagnosed with KS, while in the remaining seven cases, KS developed after the onset of bullous disease. As expected, KS worsened when corticosteroids were used. Conclusion: Bullous diseases seem to be more frequent among patients with KS, supporting the hypothesis that HHV‐8 may be involved in their pathogenesis. Therapeutic management of these cases should take into account KS‐inducing potential of corticosteroids.